The scientific features of simultaneous translation (conference translation) and the current role in the process of translation - Rakhimova Guzal Yuldashovna; Bekmetova Dilnura Kudratovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Today in our country great attention is paid to the teaching and learning of foreign languages. In the framework of the implementation of the Decree of the President of the Republic of Uzbekistan dated December 10, 2012 No PP 1875 "On measures to further improve the system of learning foreign languages" a lot of effective work is being done in our country. In addition, the organization of international conferences, symposiums and seminars in Uzbekistan, which are attended by many scholars and delegates from leading countries, will certainly increase the need for translators who have a thorough knowledge of foreign languages ​​and have sufficient knowledge and skills.